O klassifikacii ritoričeskih priemov - Skovorodnikov, Aleksandr P. (Stylistyka, 2021)
On the paper the conception of a rhetorical device (RD), suggested in the author’s previous publications is being developed. The RD means a deliberate and pragmatically motivated deviation from different varieties of the norm, which is regarded too widely as an onthological category. The onthological typology of the norms and the corresponding typology of RD are constructed on the basis of a fragmentation of the «naive world picture», which is given not by philosophical theory, but is drawn directly from the whole complex of the texts that served as a matter to research (mostly anecdotes, some Russian folk tałes, fantasy and post-modemistic fiction). As a result of the research some particular onthologies and corresponding RD types were pointed out and new terms suggest. Besides the RD classification on the onthological basis the author offers the idea that the most important significance for rhetorics is their operational classification which could disclose the system of principles (mechanisms) of RD construction. This idea is being illustrated by the examples of RD which are organized according to the principles of economy, redundancy and contamination. In addition to what is said above the paper gives a systematical characterization of the elocutive devices inherent to the genre of newspaper anecdotes.